Speech command classification based on deep neural networks - Hossain, Md. Sakib; Islam, Syed Tamzidul; Mazumder, Sujat; Joy, Ali Imran; Sakib, Md. Sadman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.